Development and Validation of an Assessment Tool for Science Lesson Plans - Canalita, Everlita E. (Education, Science, and Technology International Conference, 2025)
Effective lesson planning is a critical yet frequently under-assessed component of high-quality science instruction. Despite its importance, existing tools for evaluating science lesson plans often lack specificity, consistency, and empirical validation. This study addresses this gap by developing and validating the Lesson Plan Assessment Tool for Science (LPATS), a standardized instrument designed to assess the quality of science lesson plans and teachers’ competence in lesson planning. Grounded in established pedagogical frameworks and informed by gaps identified in the literature, the study employed a developmental research design comprising four phases: initial tool construction, expert review, iterative refinement, and validation. Qualitative input from science education experts guided the revision of indicator statements to ensure clarity, coherence, and alignment with curricular and instructional standards. Quantitative analysis of content validity, using the item-level content validity index (I-CVI), scale-level content validity index (S-CVI), and modified kappa statistics, yielded perfect agreement scores (1.00), indicating strong expert consensus regarding the tool’s relevance and clarity. These results confirm LPATS as a valid and practical instrument for evaluating science lesson plans in both pre-service and in-service teacher education contexts. Beyond assessment, the tool supports reflective teaching practice, curriculum evaluation, and instructional quality assurance. LPATS offers a research-informed, user-friendly framework that advances science education by addressing the methodological need for a discipline-specific lesson plan evaluation tool. Future studies should investigate its construct validity, inter-rater reliability, and applicability across broader educational settings and long-term impact.